PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI BEI - Sari, Wulandari Puspita; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTStock price reflects the value of a company. If the company achieves good achievement, then the share of thecompany will be demanded by investors. This research is meant to examine the influence of financialperformance which consists of Current Ratio (CR), Return on Equity (ROE), Price Earning Ratio (PER) andEarning Per Share (EPS) to the share price of the companies which are included in LQ45 index which are listedon Indonesia Stock Exchange.The population in this research has been obtained by using purposive samplingmethod on LQ45 companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. 21companies have been selected as samples by using the purposive sampling method. The analysis technique hasbeen done by using multiple linear regression; meanwhile the hypothesis test has been done by using t test and Ftest with its significance level is 5%. The classic assumption test which has been done in this research includesnormality test, multicolinearity test, autocorrelation test and heteroscedasticity test with SPSS 23application.Based on the result of the research, it has been found that parttially Current ratio does not have anyinfluence to the share price with its sigificance level > 0.05. Meanwhile, Return on Equity (ROE), PriceEarnings Ratio (PER), and Earning Per Share (EPS) give positive influence to the share price with itssignificance level < 5%. It shows that simultaneously the financial performance give significance influence to theshare price with its significance is < 0.05.Keywords: Current ratio, return on equity, price earnings ratio, earning per share, share price.